2001
DOI: 10.1103/physreva.64.042106
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle nonlocality and entanglement with the vacuum

Abstract: We propose a single-particle experiment that is equivalent to the conventional two-particle experiment used to demonstrate a violation of Bell's inequalities. Hence, we argue that quantum mechanical nonlocality can be demonstrated by single-particle states. The validity of such a claim has been discussed in the literature, but without reaching a clear consensus. We show that the disagreement can be traced to what part of the total state of the experiment one assigns to the (macroscopic) measurement apparatus. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…In this representation, the above entanglement is not apparent, and indeed it has been argued that nonlocality cannot be a single-particle effect [10] (although see Ref. [11]). As a second example, consider a two-particle state where Alice has one particle and Bob the other.…”
mentioning
confidence: 99%
“…In this representation, the above entanglement is not apparent, and indeed it has been argued that nonlocality cannot be a single-particle effect [10] (although see Ref. [11]). As a second example, consider a two-particle state where Alice has one particle and Bob the other.…”
mentioning
confidence: 99%
“…Accordingly, it is absolutely irrelevant which irreducible representation we select for our explicit calculations. These remarks apply, in particular, to all the papers on entanglement with vacuum and nonlocality of a single photon where the calculations were performed in the ∞-representation [17,18,19,20,21,22,23,24,25] (see however [26]). …”
Section: Discussionmentioning
confidence: 99%
“…This is true, but the problem with the B-representation is that the third subsystem does not have a natural decomposition into subsystems [8]. The distinction between the vacuum |0 and 'a vacuum |0 at one side of the beam-splitter' is undefined in this representation [9] since the vacuum is here unique, and corresponds to the vector (17). An entanglement with a unique vacuum must be trivial.…”
Section: B-representation Calculationmentioning
confidence: 99%
“…This came as a surprise, because single particle states show no signs of entanglement when expressed as a simple superposition of wavefunctions, and initially there were doubts as to whether single-particle quantum nonlocality is genuine. Subsequent theoretical [7][8][9][10][11][12][13] and experimental [14][15][16][17][18][19][20] investigations confirmed that single-particle QN is indeed genuine and clarified that the entanglement lies between the spatial modes, rather than between the particles (a clear and concise summary can be found in Ref. [10]).…”
Section: Introductionmentioning
confidence: 96%